Bridge asset management using Petri-Nets - Yianni, P.; Neves, Luís C.; Rama, D.; Andrews, J.; Dean, R. (2017)
Management of a diverse portfolio of assets is a demanding and complex task. Although extensive research has been carried out in bridge asset management models, the model developed in this study contains flexibility which is able to model a vast array of different types of elements, under different environmental stressors and with different operational strategies. The Petri-Net model developed contains a number of different modules interconnecting to form a robust bridge asset management modelling framework. The result is an adaptable and flexible decision making tool approach to help bridge portfolio managers.